The clinical assessment of propranolol vs. divalproex sodium in the prophylaxis of migraine at a tertiary centre in Bihar (Journal of Pharmaceutical Negative Results, 2023)
Background: Migraine headaches are common, with a worldwide prevalence ranging between 8 and 18%. The present study was conducted to compare propranolol and divalproex sodium in the prophylaxis of migraine.Aims and Objectives: The present study was conducted to compare propranolol and divalproex sodium in the prophylaxis of migraine.Materials & Methods: 80 patients of migraine were divided into 2 groups of 40 each. In group I, patients received propranolol 20 to 160 mg/day, and in group II, patients received divalproex sodium 250 to 750 mg/day for three months. The Migraine Disability Assessment Score (MIDAS) and VAS were compared. Adverse effects were also recorded.Results: There were 18 males and 22 females in group I, and group II had 24 males and 16 females. The mean ages (mean ± SD) in years were 30.46±8.5 in group I and 35.14±9.24 in group II, respectively; MIDAS was 12.4±3.62 in group I and 10.6±3.90 in group II; VAS was 7.4±1.48 in group I and 6.5±3.02 in group II; the frequency/month of migraine was 5.02±1.26 in group I and 5.01±1.64 in group II; and the duration of migraine was 20.8±6.10 in group I and 19.2±7.2 The difference was non- significant (P> 0.05). Tremor was seen in 1 in group I, hair loss in 1 in group I, weight gain in 1 in group II, insomnia in 1 in group I and 2 in group II, dizziness was seen in 3 in group I and 4 in group II and facial swelling was seen in 1 in group II. The difference was significant (P< 0.05).Conclusion: Both drugs were found to be equally effective in the management of migraine patients.